The changing face of antisemitism : from ancient times to the present day - Laqueur, Walter 1921-2018 (Oxford Univ. Press, 2006)
The new antisemitism -- Interpretations of antisemitism -- Ancient and medieval anti-Judaism -- Enlightenment and after -- Racialism and Jewish conspiracies -- Towards the Holocaust -- Contemporary antisemitism -- Assimilation and its discontents -- Antisemitism and the left -- Antisemitism and the Muslim world